The role of dehydroepiandrosterone sulfate on learning and memory in rat hippocampus and its link to the prefrontal cortex - Shaimi, Asma Ulhusna (2020)
Dehydroepiandrosterone sulfate (DHEAS) is one of the important neurosteroids that are originally synthesised in the brain. The role of DHEAS is important in enhancing learning and memory performance, and executive functions. The aim of this study was to investigate the changes of DHEAS fluorescence level corresponding to the learning and memory task and attentional performance task in real time imaging in the Cornu Ammonis 1 (CA1) area of hippocampus. In this study, adult male Sprague Dawley rats were divided into two major different groups of behavioural tasks which are Morris water maze (MWM) and 5-Choice serial reaction time task (5-CSRTT). For MWM, eight-week-old rats weighing 250-290 g whereas for 5-CSRTT, ten-week-old rats weighing 300-330 g were divided into two groups of 9 animals for control group, C (group I), and behavioural task with surgical implantation and imaging, BP (group IIa) and control with imaging, CI (group IIb) each. Fluorescence labelling was developed as a tagging to the DHEAS in the CA1 area of hippocampus for both major groups. DHEAS antibodies were fluorescently conjugated with Alexa Fluor 5-SDP ester 488 dye. Surgical implantation and fluorescence labelling were delivered into the CA1 area of hippocampus for each task. The MWM test was performed for spatial learning and memory performance by which 5 days was for the spatial learning test and on the 6th day for probe test. The 5-CSRTT test was used to determine attentional performance of executive function. Following this, the animals were anaesthetized with isoflurane and the DHEAS fluorescence wassimultaneously visualised and imaged in real time imaging with FFM probe connected to Cell Visio Lab system. The animals were dissected and their hippocampi were collected for the histological validation of the probe placement using hematoxylin and eosin (H&E) staining. The conjugation of fluorescent-labelled was the first successful report which demonstrated the degree of labelling (DOL) in the range of desired results and showed the signal of DHEAS expression on the FFM connected to the Cell Visio Lab system. Optimisation on surgical implantation was made to determine the coordinates at the CA1 area of hippocampus precisely and accurately. The results in MWM test indicated that both groups (group IIa and IIb) showed significant changes for spatial learning and memory with enhancement of DHEAS fluorescence intensity. The results revealed that DHEAS fluorescence intensity significantly increased due to spatial learning and memory performance. In the 5-CSRTT test, the results exhibited that the animals learned and tended to respond in an appropriate aperture. The results indicated attentional performance occurred and integrated with increase in the intensity of DHEAS fluorescence. Findings form this study were able to elucidate the role of DHEAS and the association between DHEAS with learning and memory performances as well as executive function thus linking the CA1 area of the hippocampus to the prefrontal cortex.